Evaluation of the efficacy of a novel perfusion solution for normothermic ex vivo lung perfusion compared with Steen solution™ (animal experimental study) - S. V. Gautier; O. M. Tsirulnikova; I. V. Pashkov; N. V. Grudinin; D. O. Oleshkevich; D. M. Bondarenko; N. P. Моzheikо; A. A. Karpov; N. S. Bunenkov (Вестник трансплантологии и искусственных органов)
Respiratory diseases, together with infectious complications and hereditary lung diseases, rank third in international mortality statistics. Today, lung transplantation is a recognized method of treating end-stage lung diseases. However, the number of transplant surgeries performed is not much. This is down to the high requirements on the condition of a potential lung donor and directly on the quality of the donor lung. This has significantly limited the number of optimal donors. Rehabilitation of donor lungs to optimal gas exchange indicators can be achieved and objectively assessed in the course of ex vivo lung perfusion (EVLP). The EVLP procedure is widespread in leading transplantation centers in Europe and North America. It allows to significantly expand the pool of donor lungs, thereby serving a greater number of patients in need of lung transplantation. The possibility of EVLP procedure using publicly available perfusion equipment was demonstrated. The optimized protocol fully demonstrated its reliability and efficiency. The developed perfusion solution had no statistically significant differences in comparison with the Steen SolutionTM, which in the future will serve as an alternative for EVLP procedure.